Research on the Whole Station's Interior Orientation Cues Oriented to Navigation Enhancement. (May 2019) - Lei, Zhu; Xianglin, Bai; Xiaohan, Tang; Yanfei, Zhang
Abstract: The large and complex interior space of multi-cabin space station makes the astronauts easily happened to navigational disorder during the travel.With the need to enhance the navigation ability of the astronauts, based on a method study on space station intra-vehicular navigation simulation including both VR visual simulation and physiological HDBR simulation, multiple different sets of sample scenes are designed for the orientation cues numbers reflected by the whole visual orientation cues that has similar form, and the specific form of the whole visual orientation cues that reflects same orientation numbers.Through the experimental data analysis, the influence law of the whole station's interior orientation cues on the navigation task performance and associated physiological effects in the cabin are obtained.